Revisão taxonômica e análise filogenética do gênero Neocarus Chamberlin & Mulaik, 1942 (Acari, Parasitiformes, Opilioacarida) - Araújo, Marcel Santos de [UNESP] (2013)
Opilioacaridae is a small and rare group of free-living mites, their biological and ecological aspects unfamiliar. Of the 37 known worldwide species, 15 are found in the New World, which 12 belong to the genus Neocarus and the other three belong to the genus Caribeacarus and can be diagnosed by the setae in the modified tarsus of palp and telotarsus I. Despite recent descriptions, there is no proposed relationship between their species. In order to fill this gap, we present the first hypothesis of phylogenetic relationships among species of Neocarus. Of the material analyzed, 20 characters and 37 terminal taxa were included in the analysis. We used NONA with 1000 replicates and 100 trees stored for replication, with equal weights of characters through the TBR heuristic search using the ACCTRAN optimization and WinClada as interface. Phylogenetic analysis produced 20 equally parsimonious trees with 73 steps, with a consistency index of 68 and a retention index of 74. The strict consensus tree had found 83 steps, consistency index 60 and 63 retention rate. To check the support of branches was used Bremer index, with 1000 replications and considering trees with 5 additional steps. The monophyly of Neocarus was not observed, being paraphyletic with respect to Caribeacarus, and the relationships between their species is not fully established, presenting polytomies. The type material of some species could not be obtained for taxonomic analysis, as well as some structures could not be observed. The Neocarus ojastii fits the diagnosis of Caribeacarus, suggesting a new combination, as well N. calakmulensis that can treat a synonymy of N. nicaraguensis